Pengaruh Sebaran Lokasi Minimarket Terhadap Jangkauan Pelayanan Pasar Tradisional di Kecamatan Banyumanik - Anggraini, Pratamaningtyas (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The number of minimarket retail business in Semarang city has increased significantly since 2009 to 2011, and has penetrated the suburban areas such as Banyumanik which is known to have been one of the city’s important housing areas. Theoretically, the community’s choice of shopping location will be affected by the retail business’ proximity; in which case the traditional markets is in direct competition with minimarket retail businesses. The study examines the minimarket retail businesses’ location’s effects on the traditional markets’ service coverage in Banyumanik District in Semarang, through nearest neighbour analysis, network analysis and spatial analysis. The study has found that minimarkets tend to be located on the main transportation routes and are scattered along the main roads therefore having a different pattern of service coverage compared to traditional markets. Analysis has also indicated that the service coverage areas of both types of trade facilities tend to overlap in several areas. The study also found that minimarkets tend to have a service coverage between 100 to 500 meters, while traditional markets between 500 to 1000 meters.